MINIMASI KELUHAN PEKERJA PADA UMKM TIRTA 88 DENGAN PERANCANGAN ALAT ERGONOMIS DAN METODE VDI 2221 - Wira Kumala; Widodo, Lamto; Sukania, I Wayan (Jurnal Mitra Teknik Industri, 2023)
Material handling is one of the things that is often a problem for both large companies and MSMEs. One example of a manual material handling problem occurs in MSMEs Tirta 88 as a provider of drinking water in gallons. The average sales of gallon refillable water at MSMEs Tirta 88 over the past 6 months is 348 gallons / day. Therefore, workers at MSMEs Tirta 88 have many complaints. The complaint data collection uses a Nordic Body Map (NBM) questionnaire. Then the work posture assessment using the Rapid Entire Body (REBA) method and the Workplace Ergonomy Risk Assessment (WERA). The design method used is VDI 2221. The results of this study are in the form of a new 3D gallon basket design that is in accordance with the anthropometry of workers in MSMEs Tirta 88 and will be implemented. Before being implemented, a 3D design simulation analysis was carried out in order to determine the decrease in Rapid Entire Body (REBA) and Workplace Ergonomy Risk Assessment (WERA) scores. The simulation results showed a decrease in the Rapid Entire Body (REBA) score to four for all postures and the Workplace Ergonomy Risk Assessment (WERA) to 35 for two postures and 30 for one posture.